Hamman’s syndrome: a case report of spontaneous pneumomediastinum after vaginal delivery - Gentile, Marco; Zinna, Mariaconcetta; Costanza, Antonio; Remo, Andrea; Sala, Giuseppe; Catapano, Pietro (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Spontaneous pneumediastinum (Hamman’s syndrome) is a rare pathology defined as the presence of free air in the mediastinum with subcutaneous emphysema without trauma or medical problem. It is also a rare complication of labour and delivery and it usually occurs in the second stage of labour. A twenty-six-year-old primigravida presented to our hospital at 39 weeks and 6 days in spontaneous labour. Two hours following the delivery the patient developed neck tightness and chest tenderness with palpation. Chest X-ray and CT scan revealed pneumomediastinum extending into the soft tissue of the neck. A conservative management was performed. Spontaneous pneumomediastinum is a rare condition with a reported incidence of less than 1:44000 and in the setting of pregnancy or labor 1:100000. Regarding pregnancy, the valsalva maneuvers produced in the second stage of labor has been implicated in the development of spontaneous pneumomediastinum. Chest X-ray (posteroanterior and lateral view) is the most important test to confirm the diagnosis. The Hamman’s syndrome has usually a benign course and the management in often conservative. A timely diagnosis of Hamman’s syndrome is necessary for patient safety and correct management, but most cases have a self-limiting course.